Effects of neutralising interleukin-6 on glucocorticoid-mediated adaptations to stress in rat skeletal muscle and liver - Wilson, Nathaniel W. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2005.